Effect of Some Medicinal Plants on the Activity of Some Immunological Factors in Saliva and Serum of Type –?? Diabetics (Baghdad Science Journal, 2025)
The study involved 45 male and 45 females of diabetic patients type- ?? aged from 40-69years , and with the same numbers of males and females for control , all the patients and controls were without any periodontal diseases and without any systemic disease. Diabetic patients were divided in to three groups according to the degree of periodontitis , and the inflamed gingiva of all groups of diabetic patients were treated with the dried fruits powder (crude) of medicinal plants Quercus robur , Thuja occidenalis , Terminalia chebula, Anethum graveolens , respectively and mixture. Some immunological and antimicrobial factors (IgA, Lactoferrin , Lysozyme ) , were detected in serum and saliva of diabetic patients and the controls , the results revealed that the level of IgA , Lysozyme in saliva were more than in serum of the control , and this will insure that these factors are considered to be generally protected against bacteria in the oral cavity . Also there was a significant increase at (p?0.001) especially after treatment with the mixture of medicinal plants , so that the mixture of these plants can be considered the best type in the treatment of inflamed gingiva of type –?? diabetic patients.